2023
DOI: 10.1523/eneuro.0204-22.2023
|View full text |Cite
|
Sign up to set email alerts
|

Different Forms of Plasticity Interact in Adult Humans

Abstract: Neuroplasticity is maximal during development and declines in adulthood, especially for sensory cortices. On the other hand, the motor and prefrontal cortices retain plasticity throughout the lifespan. This difference has led to a modular view of plasticity in which different brain regions have their own plasticity mechanisms that do not depend or translate on others. Recent evidence shows that visual and motor plasticity share common neural mechanisms (e.g. GABAergic inhibition), indicating a possible link be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 104 publications
0
4
0
Order By: Relevance
“…It is also possible that motor and visual areas have different excitability thresholds. For example, even though brain plasticity is presumed to be globally controlled through GABAergic processes in the visual (Greifzu et al, 2014; Harauzov et al, 2010) and motor (McLean et al, 1996; Schabrun & Hodges, 2012; Thapa et al, 2021; Ziemann et al, 2001) system, it has been shown that when plasticity is elicited simultaneously for the visual and motor system, motor plasticity may remain intact at the cost of visual plasticity (Sarı & Lunghi, 2023). However, the consistent findings of a correlation between PT and rMT across all our analyses, indicate that, even if qualitatively different, the two cortical excitability measures are indeed described by a linear relationship.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that motor and visual areas have different excitability thresholds. For example, even though brain plasticity is presumed to be globally controlled through GABAergic processes in the visual (Greifzu et al, 2014; Harauzov et al, 2010) and motor (McLean et al, 1996; Schabrun & Hodges, 2012; Thapa et al, 2021; Ziemann et al, 2001) system, it has been shown that when plasticity is elicited simultaneously for the visual and motor system, motor plasticity may remain intact at the cost of visual plasticity (Sarı & Lunghi, 2023). However, the consistent findings of a correlation between PT and rMT across all our analyses, indicate that, even if qualitatively different, the two cortical excitability measures are indeed described by a linear relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Forty volunteers, mean age 28.6 ± 0.72 years, 25 females (including authors I.S. and C.L) took part in experiment 1 ( Sarı & Lunghi, 2023 ). Thirty-three volunteers, mean age 25.8 ± 0.11 years, 18 females (including authors M.A.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, neuroplasticity exhibits stage-specific and modular differences. During human development, neuroplasticity is strongest; in adulthood, certain brain regions such as the sensory cortex experience a decrease in plasticity, but areas like the motor cortex, prefrontal cortex, and hippocampus maintain a high level of plasticity ( Karni et al, 1995 ; Sarı and Lunghi, 2023 ).…”
Section: Exercise-induced Neuroplasticitymentioning
confidence: 99%
“…Cortical excitation and inhibition (E/I) balance is one of the important mechanisms for maintaining its internal homeostasis and normal function. Studies have shown that patients with CLBP have disrupted E/I balance in the motor and prefrontal cortices ( Sarı and Lunghi, 2023 ), and the resulting excitability changes in the related cortices and related transmission pathways may be one of the important reasons for the persistence of pain ( Parker et al, 2016 ; Schabrun et al, 2017 ). Cortical excitability includes two forms: short-interval intracortical inhibition (SICI) and short-interval intracortical facilitation (SICF).…”
Section: A New Perspective On Exercise Therapy For Chronic Low Back P...mentioning
confidence: 99%